2005
DOI: 10.1103/physrevlett.94.197201
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Modulated Quadrupolar Structures inPrPb3

Abstract: Neutron diffraction measurements have been performed on the cubic compound PrPb(3) in a [001] magnetic field to examine the quadrupolar ordering. Antiferromagnetic components with q = (1/2 +/- delta 1/2 0), (1/2 1/2 +/- delta 0) (delta approximately 1/8) are observed below the transition temperature T(Q) (0.4 K at H = 0) whose amplitudes vary linear with H and vanish at zero field, providing the first evidence for a modulated quadrupolar phase. For H < 1 T, a nonsquare modulated state persists even below 100 m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
91
1

Year Published

2007
2007
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(93 citation statements)
references
References 31 publications
1
91
1
Order By: Relevance
“…Such a nonmagnetic ground state is known as the Γ 3 doublet in the cubic crystalline electric field (CEF) of a f 2 configuration. Intensive studies have revealed various interesting states in the cubic Γ 3 doublet systems, in particular in Pr-based intermetallic compounds [8][9][10][11][12]. However, Pr-based cubic Γ 3 doublet systems usually have well-localized quadrupole moments, and thus until quite recently there have been no study on the quadrupolar instability by tuning the c-f hybridization.…”
mentioning
confidence: 99%
“…Such a nonmagnetic ground state is known as the Γ 3 doublet in the cubic crystalline electric field (CEF) of a f 2 configuration. Intensive studies have revealed various interesting states in the cubic Γ 3 doublet systems, in particular in Pr-based intermetallic compounds [8][9][10][11][12]. However, Pr-based cubic Γ 3 doublet systems usually have well-localized quadrupole moments, and thus until quite recently there have been no study on the quadrupolar instability by tuning the c-f hybridization.…”
mentioning
confidence: 99%
“…The additional new magnetic structures that develop below the primary ordering temperature have different temperature and field dependencies than the quadrupolar order observed in PrPb 3 and therefore appear to have a different origin. 18 A quadrupolar order generally results from the degenerate orbital level which carries a quadrupolar moment. These small moments are strongly field-dependent and become stronger as the applied field is increased, which is opposite to what we observe.…”
mentioning
confidence: 99%
“…1 Nonlinear susceptibility measurements disfavored such scenario, 7 however, and indicated instead the possibility of a mixedvalence state. 8 The latter was also supported by de Haasvan Alphen measurements of uranium-doped samples of ThBe 13 . 9 The new scenario necessitates the study of the full two-channel Anderson model away from its localmoment regimes, where a low-energy Kondo-Hamiltonian description is not available.…”
Section: Introductionmentioning
confidence: 72%
“…4 The situation is similar in the case of praseodymium compounds. 5,6 For the case of UBe 13 , it was originally speculated that the Γ 3 doublet would constitute the lowest-energy ionic configuration. This opened the possibility of a quadrupolar route to two-channel Kondo physics, in which a local quadrupolar moment would be screened by conduction electrons whose spin degree of freedom would provide the two degenerate channels.…”
Section: Introductionmentioning
confidence: 99%